Relationships between pulmonary function test parameters and quantitative computed tomography measurements of emphysema in subjects with chronic obstructive pulmonary disease - Šileikienė, Virginija; Urbonas, Marius; Matačiūnas, Mindaugas; Norkūnienė, Jolita (Acta medica Lituanica, 2018)
Objective. CT is able to precisely define the pathological process in COPD. There are a number of previous articles discussing the distribution of emphysema and its connection with pulmonary function tests. However, the results obtained by the researchers are not identical. Purpose. To assess relationships between emphysema and pulmonary function test parameters in COPD patients. Materials and methods. Fifty-nine patients diagnosed to have COPD underwent chest CT examinations and pulmonary function tests. For the quantitative assessment, percentages of low attenuation volume LAV950 HU (%) of a both lungs, the right lung, the left lung, and each lobe were obtained. Quantitative CT measurements were compared with forced expiratory volume in 1 s (FEV1), the ratio of FEV1 to forced vital capacity (FEV1/FVC), the diffusing capacity for carbon monoxide (DLco) and total lung capacity (TLC). Results. Except for the right middle lobe and the right upper lobe, respectively, all the quantitative CT measurements showed weak to moderate negative correlations with diffusing capacity (DLco) (r = –0.35 to –0.61, p < 0.05) and weak positive correlations with TLC (r = 0.34 to 0.44, p < 0.05). Group analysis indicated that LAV–950 HU (%) values of both lungs, right lung, left lung, and each lobe, except for right middle lobe, were increased in patients with GOLD stages 3 and 4 of COPD compared to GOLD stages 1 and 2 (p < 0.05). Conclusion. CT measurements of emphysema are significantly related to pulmonary function tests results, particularly DLco.
Keywords: emphysema; quantitative computed tomography (CT); pulmonary function; COPD